Ways To Use Advanced Technologies in Preparing Future Technology Teachers for Professional Activity - Kadirov Bakhtiyor Eshmurzaevich (Genius Publishing Group, 2023)
This article talks about the ways of using advanced technologies in preparing the future technology teacher for professional activities.
Keywords: teacher; technology; digitalization; teaching